Analysis of Quality Control Strategy Using The Statistical Process Control (SPC) Method In The Mass Product Housing Project at Java Residence Cluster - Kukuh Budi Prasetiya; Andi Patriadi; Sajiyo Sajiyo (Pelopor Publikasi Akademika, 2025)
The advancement of industrial activities requires high-performance management to achieve desired outcomes, particularly in complex projects such as construction. This study aims to analyze the application of the Statistical Process Control (SPC) method to improve product quality in the construction project of the Java Residence Cluster in Sidoarjo. Managing cost, time, and quality remains a significant challenge in construction projects. This research focuses on identifying and addressing complaints or defects in housing units that affect the quality of the project, using SPC as a quality control method. Data were collected from primary sources, specifically from the staff of PT. Mitra Usaha Konstruksi, as well as secondary data from relevant literature. The analysis shows that the application of SPC successfully reduced the number of complaints or defects from 5.95 complaints per unit in Cluster 1 Phase 3 to 3.12 complaints per unit in Cluster 2 Phase 1, with an effectiveness rate of 52.47%. Pareto analysis identified that the majority of complaints were related to doors, windows, and wall paint, suggesting that these areas should be prioritized for improvement in future construction projects. The study recommends the continued use of SPC to improve product quality and identify the root causes of defects to ensure compliance with the developer's quality targets.